Impact of heterogeneity-corrected dose calculation using a grid-based Boltzmann solver on breast and cervix cancer brachytherapy - Hofbauer, Julia; Kirisits, Christian; Resch, Alexandra; Xu, Yingjie; Sturdza, Alina; Pötter, Richard; Nesvacil, Nicole (Journal of Contemporary Brachytherapy, 2016)
Purpose : To analyze the impact of heterogeneity-corrected dose calculation on dosimetric quality parameters in gyne¬cological and breast brachytherapy using Acuros, a grid-based Boltzmann equation solver (GBBS), and to evaluate the shielding effects of different cervix brachytherapy applicators. Material and methods: Calculations with TG-43 and Acuros were based on computed tomography (CT) retrospectively, for 10 cases of accelerated partial breast irradiation and 9 cervix cancer cases treated with tandem-ring applicators. Phantom CT-scans of different applicators (plastic and titanium) were acquired. For breast cases the V<sub<20Gyαβ3 to lung, the D 0.1cm³ , D 1cm³ , D 2cm³ to rib, the D 0.1cm³ , D 1cm³ , D 10cm³ to skin, and D max for all structures were reported. For cervix cases, the D 0.1cm³ , D 2cm³ to bladder, rectum and sigmoid, and the D 50 , D 90 , D 98 , V 100 for the CTV HR were reported. For the phantom study, surrogates for target and organ at risk were created for a similar dose volume histogram (DVH) analysis. Absorbed dose and equivalent dose to 2 Gy fractionation (EQD2) were used for comparison. Results : Calculations with TG-43 overestimated the dose for all dosimetric indices investigated. For breast, a decrease of ~8% was found for D 10cm³ to the skin and 5% for D 2cm³ to rib, resulting in a difference ~ –1.5 Gy EQD2 for overall treatment. Smaller effects were found for cervix cases with the plastic applicator, with up to –2% (–0.2 Gy EQD2) per fraction for organs at risk and –0.5% (–0.3 Gy EQD2) per fraction for CTV HR . The shielding effect of the titanium applicator resulted in a decrease of 2% for D 2cm³ to the organ at risk versus 0.7% for plastic. Conclusions : Lower doses were reported when calculating with Acuros compared to TG-43. Differences in dose parameters were larger in breast cases. A lower impact on clinical dose parameters was found for the cervix cases. Applicator material causes systematic shielding effects that can be taken into account.